The Effect of Human Resource Development, Work Capability on Work Ethic and Employee Performance - Mubaraq, Arya Fadh; Kamaluddin, Murdjani; Ruslan, Ruslan (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Satisfactory performance does not occur automatically, therefore an assessment of the work carried out by employees is required. The purpose of this research is to test and analyze the influence of HR development on employee work ethic, HR development on employee performance, work ability on employee work ethic, work ability on employee performance, work ethic on employee performance, the role of work ethic in mediating the influence of human resource development on employee performance and the role of work ethic in mediating the influence of ability on employee performance. This research was conducted at BPPW, BPJN and BP2JK Southeast Sulawesi. The number of respondents to this research was 183 people, consisting of 59 BPPW employees, 100 BPJN employees and 24 BP2JK Southeast Sulawesi employees. This research uses quantitative descriptive analysis methods. The results of the research are; HR development has a positive and significant effect on employee work ethic, HR development has a positive and significant effect on employee performance, Work ability has a positive and significant effect on employee work ethic, Work ability has a positive and significant effect on employee performance, Work ethic has a positive and significant effect on performance employees, work ethic can mediate the influence of human resource development on employee performance, work ethic can mediate the influence of work ability on employee performance.